Pengaruh FEAR OF MISSING OUT (FOMO) Dan Hedonic Shopping Motivation Terhadap Impulse Buying Di E-Commerce (Studi Pada Generasi Z Lombok) - Soleha, Siti Rahmaniatun; H. Junaidi Sagir, H. Junaidi Sagir (ALEXANDRIA (Journal of Economics, Business, & Entrepreneurship), 2024)
This research aims to test and analyze the effect of Fear Of Missing Out (FOMO) and Hedonic Shopping Motivation on Impulse Buying in E-Commerce (Study on Generation Z Lombok). The sample in this research amounted to 100 samples. The sampling technique in this research used non-probability sampling technique with purposive sampling method. Data analysis in this research used multiple linear regression analysis and all analysis in this research was processed using SPSS Statistic version 25. The results of statistical testing and data analysis show that the indicators in the research conducted are declared valid where in the classical assumption test, the data is normally distributed and there is no multicollinearity. The results of this research also show that the two independent variables, namely Fear Of Missing Out (FOMO) and Hedonic Shopping Motivation, have a positive and significant influence on the dependent variable, namely Impulse Buying.